2000
DOI: 10.1159/000012117
|View full text |Cite
|
Sign up to set email alerts
|

Microsatellite Instability in Thyroid Papillary Carcinoma and Multinodular Hyperplasia

Abstract: Microsatellite instability (MSI) is a molecular landmark of mutations in DNA mismatch repair genes. The impaired efficiency of DNA repair mechanisms promotes carcinogenesis as well as contributes to tumour progression. Until now, only few studies on MSI in thyroid tumours have been published. Therefore, the aim of the present study was to investigate MSI as a possible characteristic feature of thyroid tumours. The analysis of 12 thyroid papillary carcinomas and 17 multinodular hyperplasias at 13 microsatellite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0
2

Year Published

2002
2002
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 23 publications
0
6
0
2
Order By: Relevance
“…Thyroid cancer, the most common endocrine cancer, has been shown to display aneuploidy, one form of genetic instability (Taruscio et al, 1994). Earlier cytogenetic studies measuring loss of heterozygosity (LOH) in thyroid tumours demonstrated greater overall prevalence of LOH in malignant lesions than in benign pathologies (Barril et al, 2000;Dobosz et al, 2000) with greatest LOH rates evident in the more aggressive cancers. The majority of earlier studies have investigated gross chromosomal changes, due primarily to absence of reliable techniques to measure smaller intrachromosomal mutations.…”
mentioning
confidence: 99%
“…Thyroid cancer, the most common endocrine cancer, has been shown to display aneuploidy, one form of genetic instability (Taruscio et al, 1994). Earlier cytogenetic studies measuring loss of heterozygosity (LOH) in thyroid tumours demonstrated greater overall prevalence of LOH in malignant lesions than in benign pathologies (Barril et al, 2000;Dobosz et al, 2000) with greatest LOH rates evident in the more aggressive cancers. The majority of earlier studies have investigated gross chromosomal changes, due primarily to absence of reliable techniques to measure smaller intrachromosomal mutations.…”
mentioning
confidence: 99%
“…Subsets of hyperplastic nodules have been shown to contain many of the histological features associated with thyroid cancer, can be monoclonal in origin, and demonstrate microsatellite instability. [21][22][23] Furthermore, several studies have suggested a higher incidence of thyroid cancer in the setting of hyperplastic nodules, although definitive evidence is lacking. 24,29,30 Thus, the role hyperplastic nodules may have in thyroid tumorigenesis and their preneoplastic potential remain uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…21 Moreover, microsatellite instability, a hallmark of genomic instability associated with tumorigenesis, was shown to be present in 35% of cases of multinodular hyperplasia. 23 Similarly, several studies have suggested a higher incidence of thyroid cancer in patients with multinodular goiter, although definitive data are lacking. 24 These findings suggest a potential premalignant status, at least in a subset of nodules of FTH.…”
mentioning
confidence: 99%
“…This DNA lesion is detected by the cell, activating the p53 pathway, which is commonly intact in differentiated thyroid carcinoma cells [210]. DNA ruptures, there is reason to believe that residual thyroid cancer is susceptible to the effects of beta irradiation, more than the surrounding normal tissue, although there are still no in vitro or clinical data to support this hypothesis [213].…”
Section: Adjuvant Treatmentmentioning
confidence: 99%